PERAN GURU DALAM PEMBENTUKAN KARAKTER ANAK USIA DINI DI PAUD INSAN CENDEKIA - Ana Novitasari; Agus Saputra; Otri Amelia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Amelia Otri,2025. “The Role of Teachers in Shaping Early Childhood Character Through at PAUD Insan Cendekia ". Essay. Dharmasraya: Early Childhood Education Teacher Education Study Program, Dharmas University, Indonesia. This research is motivated by the importance of the teacher's role in shaping the character of early childhood through appropriate learning methods, one of which is storytelling Character building in early childhood is a crucial aspect that supports children's holistic development. Early childhood is a golden period during which moral and social values begin to take root. Teachers play a strategic role in instilling these character values through various learning methods suited to children's developmental stages, one of which is storytelling. Storytelling serves not only as an entertaining learning medium but also as a tool that conveys moral messages capable of shaping children's positive attitudes and behavior. At PAUD Insan Cendekia. This study aims to describe the role of teachers in shaping the character of early childhood through storytelling methods at PAUD Insan Cendekia. Character education is a vital foundation in a child's development, especially during early childhood, which is a golden period for personality formation. The storytelling method was chosen for its strong appeal to children and its effectiveness in conveying moral values in an enjoyable and understandable way. This research uses a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. The results show that teachers play a central role as educators, storytellers, and role models in instilling character values such as honesty, responsibility, empathy, and cooperation. Through engaging and interactive storytelling, teachers are able to build emotional closeness and internalize positive values in children's daily lives. In conclusion, storytelling is an effective strategy to support the teacher's role in shaping children's character from an early age.